Improved properties of 3d transition metal nanoclusters deposited on defective hexagonal boron nitride quantum dots. (December 2022) - Montejo-Alvaro, F.; Vásquez-López, A.; López-Fermín, D.M.; Rojas-Chávez, H.; Medina, D.I.; Franco-Luján, V.A.; Cruz-Martínez, H.
Abstract: Density functional theory calculations were used to investigate the stability and reactivity of icosahedral Fe13, Co13, Ni13, and Cu13 nanoclusters deposited on pristine and defective hexagonal boron nitride quantum dots (h-BNQDs). The defective h-BNQDs were studied with a N vacancy (h-BNV QDs) and a B vacancy (h-BV NQDs). The binding energy between the Fe13, Co13, Ni13, and Cu13 nanoclusters and pristine and defective h-BNQDs indicates that the stability of the Fe13, Co13, Ni13, and Cu13 nanoclusters deposited on defective h-BNQDs is higher than those deposited on pristine h-BNQDs. Therefore, defective h-BNQDs are better support material for these nanoclusters. Typically, it is observed that the charge is transferred from metal nanoclusters to pristine and defective h-BNQDs. On the reactivity of the metal nanoclusters deposited on pristine and defective h-BNQDs, the nanoclusters/h-BNQDs composites exhibit similar HOMO–LUMO gaps than bare nanoclusters. Consequently, the formation of nanoclusters/h-BNQDs composites is a good strategy to improve the reactivity of h-BNQDs. Graphical Abstract: 3 d transition metal nanoclusters deposited on defective hexagonal boron nitride quantum dots. ga1